Lupus-like eruption as the presenting sign of acute myeloblastic leukemia. (March 2016) - Cedeno-Laurent, F; Obstfeld, A E; Boni, A; Lipoff, J B
Cutaneous manifestations are often the presenting sign of internal malignancies. Up to 50% of patients with acute myeloblastic leukemia (AML) have skin findings. Connective tissue disease, particularly dermatomyositis and, rarely, lupus, have been reported as a paraneoplastic syndrome to various internal malignancies, but seldom with leukemias. We report the case of a middle-aged woman ultimately diagnosed with acute myeloblastic leukemia, who presented initially with a malar eruption, joint pains, and diffuse rash on the upper and lower extremities, with pathology consistent with lupus erythematosus and negative autoimmune serology. There are no prior reports of cutaneous lupus as the presenting sign of AML, and this case highlights the importance of considering paraneoplastic phenomena with presentations of connective tissue disease in older patients, especially with negative serology.